Chemical Composition, Antimicrobial and Antioxidant Activity of Echinophora platyloba DC - Zahra Pilevar; Hedayat Hosseini (Journal of Pharmacy and Nutrition Sciences, 2013)
The existence of artificial additives in food seems to be unhealthy from the consumers’ point of view, and it is why scientists are looking for some solutions to reduce the unhealthy varieties of additives in manufactured products. This article presents a revision of studies published in recent years on this topic and looks at possible future trends in the sector on one of the indigenous plant activities, which is used as a food seasoning in Iran. Echinophora platyloba DC has a high potency to act as an antimicrobial and antioxidant at the same time. In 3 sections this article explains the subject as follows. The first part includes determination of chemical constituents of isolated fresh and dry aerial parts by different extraction methods. They were analyzed by Gas Chromatography. In the second part antibacterial and antifungal activity of both plant extracts and its essential oil were evaluated against gram positives and gram negatives followed by fungus. Finally in the last part, antioxidant properties of the plant are mentioned. The essential oil and the crude extracts from E. platyloba species are of active candidates which can be used as antioxidant, antimicrobial agents so they still would be the novel ones for further researches.